2015
DOI: 10.1002/anie.201411914
|View full text |Cite
|
Sign up to set email alerts
|

A Defined α‐Helix in the Bifunctional O‐Glycosylated Natriuretic Peptide TcNPa from the Venom of Tropidechis carinatus

Abstract: Natriuretic peptides (NP) play important roles in human cardiac physiology through their guanylyl cyclase receptors NPR-A and NPR-B. Described herein is a bifunctional O-glycosylated natriuretic peptide, TcNPa, from Tropidechis carinatus venom and it unusually targets both NPR-A and NPR-B. Characterization using specific glycosidases and ETD-MS identified the glycan as galactosyl-β(1-3)-N-acetylgalactosamine (Gal-GalNAc) and was α-linked to the C-terminal threonine residue. TcNPa contains the characteristic NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, a natriuretic peptide isolated from Krait venom (known as KNP), was reported to have a putative α-helix, formed by its extended C-terminus [ 144 ]. Another study reported an O -glycosylated natriuretic peptide (TcNPa), from the venom of Tropichedis carinatus , and NMR analysis of TcNPa confirmed the presence of an α-helix as well [ 145 ].…”
Section: Snake Venom Peptides and Their Potential Pharmacological mentioning
confidence: 99%
“…However, a natriuretic peptide isolated from Krait venom (known as KNP), was reported to have a putative α-helix, formed by its extended C-terminus [ 144 ]. Another study reported an O -glycosylated natriuretic peptide (TcNPa), from the venom of Tropichedis carinatus , and NMR analysis of TcNPa confirmed the presence of an α-helix as well [ 145 ].…”
Section: Snake Venom Peptides and Their Potential Pharmacological mentioning
confidence: 99%
“…An O-linked glycosylated natriuretic peptide isolated from T. carinatus showed drug lead potential by demonstrating bi-functionality to both NPR-A and NPR-B natriuretic peptide receptors [52]. Furthermore, the peptide showed α-helix secondary structure and relative stability in plasma and trypsin solution.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…More recently, TcNPa isolated from T. carinatus venom was found to be the first member of the NP family to possess a significant secondary structure involving an α-helix. TcNPa has other interesting characteristics including an O -glycosylation site, activity at both NPR-A and NPR-B and strong resistance to proteolytic degradation in plasma [ 47 ]. Crystallographic structures of hNPR-C bound hCNP and hNPR-A bound hANP implicated the highly conserved residues within the NP internal ring as the likely pharmacophoric residues [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have also highlighted the importance of post-translation modifications in modulating physiological activities of NPs. Reeks [ 47 ] described the first glycosylated NP in the venom of Tropidechis carinatus , TcNPa, and a recent glycoproteomics study [ 60 ] discovered O -glycans on mature human and mammalian NPs with two glycosites in ANP positioned in the highly conserved ring region. These post-translational modifications on mature ANP were found to have a major impact on stability and circulation time of ANP as well as receptor activation in vitro and in vivo [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation